"Subjectivity in the Borderlands" - Šesnić, Jelena (2005)
The article traces the difference in the use of two critical concepts in American studies, those of the frontier and the borderlands, and tries to show how they inflect differently the project of representing new forms of subjectivity in recent US literary texts. The article also addresses the conjunction of language, genres and representations of subjectivity in Mexican American fictional texts.
Projekt MZOS
ENG